DESAIN SISTEM PEMBANGKIT LISTRIK TENAGA HYBRID MICROHYDRO PV ARRAY DI DUSUN SADAP BANGKA TENGAH - Wahri Sunanda (Jurnal Arus Elektro Indonesia, 2017)
Abstract To serve the needs of electricity, villagers rely on microhydro renewable energy with 40kW capacity, which was built with APBN budget funds in 2007. Average powerper day of Sadap mounted to 722.78 Watts/KK. From the analysis that has been done, the results of modeling for system with daily load of 130.1kWh with the lowest NPC based on simulation results using HOMER are as follows:1 microhydro power unit 19kW, photovoltaic array with a total capacity of 4kW, 48 units of 12 Volt 83.3 Ah battery ,and 6kW of bidirectional converter. Contribution of microhydro electric energy produced amounted to 155.775kWh/yr, or about 96,78% and the electrical energy produced by the photovoltaic array is equal to 5.179kWh/yr, or about 3,22%, so that the total contribution of both plants when 100% is equal to 160.954kWh/yr. The configuration is set as the most optimal based on the lowest NPC total is Rp.938.310.656,00 and levelized COE isRp1.528,500/kWh with an initial capital required for the realization of this hybrid power generation system is Rp.403.968.000,00. Keywords: hybrid power plants, microhydro, photovoltaic array, HOMER.